Methoxyflurane for Relief of Procedural Pain in Burn Patients: A Prospective Single-Centre Evaluation Study - Andreas Creutzburg; Martin R. Vestergaard; Pernille Pape; Caroline Hjelmdal; Filip Rangatchew; Rikke Holmgaard; Lars S. Rasmussen (MDPI AG, 2022)
Background: Procedural pain in burn patients continues to be a major problem. Frequently used analgesics, such as opioids, may have various side effects, including respiratory depression, nausea, and vomiting. Inhaled methoxyflurane has been used in the pre-hospital setting for trauma-related pain. This pilot study aimed to investigate the feasibility of using methoxyflurane for pain relief during dressings changes for burns in the hospital setting. Methods: In this investigator-initiated pilot study, we included burn patients undergoing dressing changes in the burn ward. The primary outcome was the maximal pain level experienced by the patient during the procedure on a verbal rating scale of 0 to 100. Furthermore, patient satisfaction and the nurse's assessment of the patient's pain were reported. We also reported the presence of nausea, vomiting, coughing, and headache, along with changes in the pulse rate, oxygen saturation, and arterial blood pressure. Results: We included 12 patients in the period of June 2021 to July 2022. The median patient-reported maximal procedural pain was 60 (interquartile range (IQR), 37-80), which corresponded well with the nurse's rating of a median of 57 (IQR 28-67). The patients were satisfied with methoxyflurane as an analgesic, with a median score of 96 (IQR 96-100). One patient reported coughing after the procedure, and another patient experienced nausea one week after the procedure. No clinically important haemodynamic changes during administration were detected. Conclusions: Methoxyflurane was found to be feasible for pain relief in burn patients undergoing dressing changes in the burn ward.